Uso de relatórios gerenciais e desempenho de vendas em companhia seguradora - Duque, Bruno da Silva (2016)
This research studies the associations between the use of management reports for business managers of a Brazilian insurance company, the perception of benefits of these reports and sales performance. As well as other national and international studies, it analyzes the use of management reports for operational managers, not by the senior management of the company. Therefore, we adopted the model of Mahama and Cheng (2013) and Widener (2007) for measuring the perceived benefits of using management reports. It also performed an analysis of quantitative data, combining data obtained through survey and historical data of the studied company (secondary data). The results showed that there is a statistically significant relationship between perceived benefit of management reports, intensity of use and the intensity of use is associated with higher sales performance. These results were observed using a structural equation model for the sample. It was also used a multiple linear regression model to analyze the correlation between the use of reports and superior performance in sales, having experience in the company itself as a control variable, and the results also showed statistics and significant relationships. The main limitation of this study is the fact that the tool used by the company to provide these reports (a mobile app) is relatively new, so the degree of predictability of the multiple linear regression model is still low and the same with the model structural equation. On the other hand, the results generate important insights for the company, the main one being the need for the new tool institutionalization and potential gains that this measure could bring.